Against All Odds: Exploring Indonesian Teachers’ Emotional Geographies in Online Teacher Professional Development - Taloko, Johanes Leonardi (SALEE: Study of Applied Linguistics and English Education, 2025)
This study explores the emotional experiences of a successful Indonesian in-service EFL teacher participating in an online teacher professional development (OTPD) program amid the dual crises of the COVID-19 pandemic and Cyclone Seroja. While prior research has explored teacher emotions during emergency remote teaching, little is known about how teachers negotiate emotional resilience under simultaneous global and local disasters. Using narrative inquiry and Hargreaves’s emotional geography framework, data were collected through virtual interviews and messaging, and then analyzed thematically. The findings highlight five emotional dimensions—physical, moral, sociocultural, professional, and political—that shaped the teacher’s journey. Despite life-threatening challenges, the participant demonstrated emotional resilience through intrinsic motivation, strong social support, and deep religious faith. These coping strategies enabled him to continue his professional development against tremendous odds. This study emphasizes the significance of acknowledging emotional geographies in OTPD, particularly in disaster-prone regions. It offers practical implications for educational institutions and policymakers to enhance teacher well-being by fostering empathy, flexibility, and support systems in professional learning programs.